2016
DOI: 10.1158/1078-0432.ccr-16-1192
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Pathway Inhibitors Sensitize BRAF-Mutant Melanoma to an Antibody-Drug Conjugate Targeting GPNMB

Abstract: Purpose: To determine if BRAF and/or MEK inhibitor-induced GPNMB expression renders melanomas sensitive to CDX-011, an antibody-drug conjugate targeting GPNMB. Experimental Design: The TCGA melanoma dataset was interrogated for a panel of MITF-regulated melanosomal differentiation antigens, including GPNMB. BRAF mutant melanoma cell lines treated with BRAF or MEK inhibitors were assessed for GPNMB expression by RT-qPCR, immunoblot and FACs analyses. Transient siRNA-mediated knockdown approaches were used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
2
38
1
Order By: Relevance
“…Three properties support this function. First, TYRP1 is highly expressed in most melanoma 28,29,45,46 . Second, the SNP rs683 genetically determines TYRP1 miRNA sponge activity.…”
Section: Discussionmentioning
confidence: 99%
“…Three properties support this function. First, TYRP1 is highly expressed in most melanoma 28,29,45,46 . Second, the SNP rs683 genetically determines TYRP1 miRNA sponge activity.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting MITF High /differentiated cells is also possible using a drug-conjugated antibody against GPNMB, a melanosomal antigen ( Fig. 4; Rose et al 2016;Ott et al 2017). Combined with approaches specifically aimed at the MITF Low dedifferentiated or NCSC populations these agents may prove useful in eradicating the MAPK pathway inhibitor-refractory pool of cells and convert targeted antimelanoma therapy into a curative approach.…”
Section: Implications and Opportunities For Therapymentioning
confidence: 99%
“…Preclinical data have demonstrated that gpNMB expression is upregulated in melanoma cell lines after exposure to the MEK inhibitor trametinib, and the combination of glembatumumab vedotin with MEK and BRAF inhibitors (trametinib with or without dabrafenib) enhanced tumor regression in xenograft models . MAPKi therapy in patients with melanoma induced the upregulation of gpNMB transcripts in tumors and increased levels of soluble gpNMB in serum . Although the high expression of gpNMB in melanoma cells observed in the current study may limit this strategy in melanoma, an association of antitumor activity with gpNMB expression was observed in patients with advanced breast cancer who received treatment with glembatumumab vedotin .…”
Section: Discussionmentioning
confidence: 61%
“…A potential rational strategy for further development of glembatumumab is the combination with mitogen‐activated protein kinase (MAPK) inhibitors (MAPKi) such as BRAF, MEK, and extracellular signal‐regulated kinase (ERK) inhibitors. Preclinical data have demonstrated that gpNMB expression is upregulated in melanoma cell lines after exposure to the MEK inhibitor trametinib, and the combination of glembatumumab vedotin with MEK and BRAF inhibitors (trametinib with or without dabrafenib) enhanced tumor regression in xenograft models . MAPKi therapy in patients with melanoma induced the upregulation of gpNMB transcripts in tumors and increased levels of soluble gpNMB in serum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation